Pengembangan LKPD Menulis Teks Eksposisi Berbasis Model Discovery Learning untuk Siswa Kelas VIII SMP/MTs - Hidayatulloh, Fariz; Zain, M. Yanuardi; Angraini, Fitri (Lentera: Jurnal Ilmiah Kependidikan, 2025)
This research relates to the development of the LKPD in writing an exposition text based on discovery learning model. It is aimed to produce a teaching material, to describe the properness of the teaching material, and to investigate the effectiveness of the teaching material, which is the development of LKPD in writing an exposition text based on discovery learning model. The method of this research was adapted from 7 of 10 steps in the research procedure and development according to Borg and Gall. The result showed that 1) this research was successful to develop a teaching material which was LKPD in writing an exposition text based on discovery learning model, 2) the overall participant activities sheet was valid according to the material expert, media expert, and practitioner with the percentage values of 93, 80, 93.3, 3) the participant activities sheet was effective to improve the ability to write an exposition text in each school with the n-gain values of 0.48, 0.44, and 0.54 in which they were included in the medium category.